Forms of Consciousness and Resistance in Native Adult Learners - Dieleman, Marinus (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1992)
This paper examines forms of consciousness and resistance displayed by Native adult learners in a community college setting. These are examined in the context of the college′s “takeover” of what was once a Native education department conceived and constructed by a Native political group. Current forms of consciousness and resistance within the college take the form of contestations over meaning rather than contestations over power. The paper suggests that inter- and intragroup variations in forms of consciousness and resistance are linked to forms of symbolic capital such as linguistic competence displayed by the students. Such a variation, it is suggested, may have implications for community development and the move towards self-govemment.